Neural responses to dynamic multimodal stimuli and pathology-specific impairments of social cognition in schizophrenia and depression. (March 2015) - Regenbogen, Christina; Kellermann, Thilo; Seubert, Janina; Schneider, Daniel A.; Gur, Raquel E.; Derntl, Birgit; Schneider, Frank; Habel, Ute
Abstract : Background: Individuals with schizophrenia and people with depression both show abnormal behavioural and neural responses when perceiving and responding to emotional stimuli, but pathology-specific differences and commonalities remain mostly unclear. Aims: To directly compare empathic responses to dynamic multimodal emotional stimuli in a group with schizophrenia and a group with depression, and to investigate their neural correlates using functional magnetic resonance imaging (fMRI). Method: The schizophrenia group ( n = 20), the depression group ( n = 24) and a control group ( n = 24) were presented with portrait-shot video clips expressing emotion through three possible communication channels: facial expression, prosody and content. Participants rated their own and the actor's emotional state as an index of empathy. Results: Although no group differences were found in empathy ratings, characteristic differences emerged in the fMRI activation patterns. The schizophrenia group demonstrated aberrant activation patterns during the neutral speech content condition in regions implicated in multimodal integration and formation of semantic constructs. Those in the depression group were most affected during conditions with trimodal emotional and trimodal neutral stimuli, in key regions of the mentalising network. Conclusions: Our findings reveal characteristic differences in patients with schizophrenia compared with those with depression in their cortical responses to dynamic affective stimuli. These differences indicate that impairments in responding to emotional stimuli may be caused by pathology-specific problems in social cognition.